An integrated future approach for the energy security of Pakistan: Replacement of fossil fuels with syngas for better environment and socio-economic development. (March 2022) - Kanwal, Saira; Mehran, Muhammad Taqi; Hassan, Muhammad; Anwar, Mustafa; Naqvi, Salman Raza; Khoja, Asif Hussain
Abstract: Energy security necessitates the continuous availability of sufficient supply in different forms at economical prices. Energy security is a priority for states like Pakistan since it is a prerequisite for socioeconomic development. Pakistan's electricity demand is gradually increasing, and the country is being challenged with significant natural gas supply-demand deficit. Thar fossil fuel reserves, mostly coal reserves will play a critical role in meeting energy needs for decades. This study aimed to provide framework for tapping indigenous alternate energy resources to address growing natural gas crisis in Pakistan for sustainable energy security. This study may aid in understanding the value of oil, energy protection, and natural gas scarcity in Pakistan, the impact of gas shortages on energy security, syngas as a natural gas substitute, syngas production through coal gasification technology, coal gasification as a high-performance low-emission solution, and syngas applications for long-term energy security. Highlights: Risks associated with energy security of Pakistan. Syngas as a substitute to natural gas/LNG in Pakistan. Understanding relationship between natural gas crisis and socio-economic development. Coal reserves of Pakistan in terms of mining, coal quality and regional perspectives. Applications of syngas for power production and as transportation fuel.